2017
DOI: 10.1016/j.jpainsymman.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Undertreatment of Cancer Pain With Analgesic Drugs on Patient Outcomes: A Nationwide Survey of Outpatient Cancer Patient Care in Taiwan

Abstract: One-third of Taiwanese outpatients experienced pain because of undertreatment. Awareness of the prevalence of undertreatment of cancer pain and identification of the vulnerable subjects may assist in enhancing patient care and improving patient's QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 30 publications
6
31
2
Order By: Relevance
“…Several authors have used PMI to assess the prevalence of undertreatment of pain, defined as a negative PMI (9,(19)(20)(21)(22). This approach has been criticized since the original purpose of PMI was to measue physicians' responses to patients` pain, not undertreatment (23).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have used PMI to assess the prevalence of undertreatment of pain, defined as a negative PMI (9,(19)(20)(21)(22). This approach has been criticized since the original purpose of PMI was to measue physicians' responses to patients` pain, not undertreatment (23).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our study showed that early initiation of chemotherapy for patients presenting with tumor pain at diagnosis provided a survival benefit over delayed treatment. Pain is one of the most prevalent distressing symptoms in cancer patients, especially for those with unresectable pancreatic cancer . Undertreatment of tumor pain had been reported as a negative predictor for quality of life and survival outcome in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is one of the most prevalent distressing symptoms in cancer patients, especially for those with unresectable pancreatic cancer . Undertreatment of tumor pain had been reported as a negative predictor for quality of life and survival outcome in cancer patients. In lung cancer, patients receiving standard oncology care integrated with early palliative care for adequate symptom control resulted in a longer survival time and a better quality of life .…”
Section: Discussionmentioning
confidence: 99%
“…Although international guidelines for cancer pain management have been established for decades, [4] , [5] , [6] inappropriate care for cancer pain remains common and is reported in approximately 40% of patients. [7] , [8] , [9] Inappropriate cancer pain management is multifactorial. 10 , 11 The average consumption of opioids is extremely low in Asia compared with Europe and North America because the availability of appropriate opioids has been limited by regulatory problems and import difficulties, which is a major barrier to adequate cancer pain management.…”
Section: Introductionmentioning
confidence: 99%